Interactive Learning Media Arrange Animal Names Based on Android Game - Nur Khafidhoh; Ichwanda Ahmad Noviandy (NEWTON: Networking and Information Technology, 2022)
The game is one of the important factors in the growth of children. Utilization and use of educational games can support the learning process of children. With the educational games, it is hoped that children's enthusiasm for learning will be more motivated. Educational games can create a pleasant atmosphere in the child's learning process. The images, music and sounds that appear make the child not feel bored, because the nature of the child likes to be bored when learning to use the written form. The making of the game "Arrange Animal Names" is designed with HTML5-based Construct 2. This game has a learning mode that will display several types of animals and their names when pressed. In this game there is also a play mode that will display pictures of animals and some letters that must be arranged correctly according to the name of the animal displayed. At the game creation stage there are several stages such as game design, menu design and character objects. So that the game "Arrange Animal Names" is produced that can be run on Android-based smartphones.